Identification of candidate genes harboring pathogenic variants in congenital heart disease and laterality defects in Chinese population - Jinxin Wang; Jinxin Wang; Weicheng Chen; Weicheng Chen; Xianghui Huang; Xianghui Huang; Xianghui Huang; Han Gao; Han Gao; Zhiyu Feng; Zhiyu Feng; Chaozhong Tan; et al. (Frontiers in Genetics)
ObjectiveCongenital heart disease (CHD) is often accompanied by laterality defects (LD), giving rise to a severe and intricate form of congenital anomaly. The aim of this study was to explore the genetic etiology of CHD/LD in the Chinese population.MethodsWe recruited 52 Chinese CHD family trios between January 2008 and August 2019, each comprising a CHD/LD proband and their healthy parents. Whole exome sequencing (WES) was carried out on peripheral blood samples from these trios. Candidate genes harboring pathogenic variants were determined through quality control of WES results and a screening approach based on variant rarity, deleteriousness, inheritance patterns, and gene function.ResultsA total of two candidate genes and 46 CHD-related genes harboring LOF (loss-of-function) variants were identified. These included one de novo variants (in DNAH2), two compound heterozygous variants (in DNAH2), and one X-linked recessive variants (in FLNA). Significantly, cilia-related genes DNAH2 had the highest frequencies of variants. Additionally, 26.1% (12/46) of CHD-related genes harboring LOF variants were significantly linked to cilia function.ConclusionThis research identified two novel candidate genes (DNAH2, and FLNA) for CHD/LD in the Chinese population, with DNAH2 ciliary genes being the most frequently occurring among all candidate genes. The results offer critical insights into the genetic basis of CHD/LD in the Chinese population, which may have implications for genetic counseling and prenatal prevention.